Cryptography- An ideal solution to privacy, data integrity and non-repudiation - Mekuria, Getahun; Adugna, Eneyew; Rajan, Deva (Zede Journal of Ethiopian Engineers and Architects, 2023)
Information Secrecy deals with maintaining privacy through encryption, data integrity through hashing and non-repudiation through digital signalures; and has become the issue of today’s communication engineering due to increasing failures to the secrecy of messages conveyed on a given networking system thereby creating damages beyond expectations. Encryption, hashing and digital signatures are the three primitives of Cryptography and these have been treated in depth and their performances on text data and image data have been studied The most secure algorithms so far in use have been introduced and the respective performance of each primitive ’s algorithm on text data and image data have been studied. Performance differences for the two data types have also been noted and outlined in detail.